The Process of Developing Religious Tolerance to Modern Science Approach - Ponjulsakdi, Orawan; Vādakovidho , Dr.Phra Pramote (Journal of Dhamma for Life, 2023)
This article aims to study the process of developing religious tolerance according to modern science. Buddhism emphasizes universal principles that all religions around the world can use to inspire and foster love, build harmonious relationships, and build trust and affection within communities. Emphasis on teachings such as love and kindness, non-violence of the rights of others, and mutual assistance. Islam emphasizes the concept of patience as a fundamental virtue. It encourages seeking help from Allah, maintaining true honesty and adherence to the teachings of the Qur'an and its principles of practice. The five principles of Islamic practice are pledge, paying zakat, prayer, fasting or ordination, and penance. Christianity has emphasized principles such as love, forgiveness, and compassion. Encouragement to follow the teachings of Christ and to live harmoniously in the Christian community. The tenets of Christianity focus on devotion to charity, prayer, fasting, and pilgrimage. In summary, all three religions emphasize the development of religious tolerance by recognizing the importance of being good and having the moral qualities of each religion. Promoting coexistence in a multicultural society that is benevolent, helpful, and does not violate the rights of others. Building unity, tolerance, and adherence to religious doctrines, these principles contribute to the peaceful coexistence of one's culture. And understanding the context within the Scriptures is essential for understanding the correct principles.